Chemerin Is a Valuable Biomarker in Patients with HCV Infection and Correlates with Liver Injury - Georg Peschel; Jonathan Grimm; Karsten Gülow; Martina Müller; Christa Buechler; Kilian Weigand (Diagnostics, 2020)
Hepatitis C virus (HCV)-induced inflammation contributes to progressive liver disease. The chemoattractant protein chemerin is associated with systemic inflammation. We hypothesized that chemerin is a biomarker that predicts the severity of liver disease in HCV patients. Furthermore, we investigated whether serum chemerin levels change during the course of HCV treatment using direct-acting antivirals (DAAs). Therefore, we measured serum concentration of chemerin in a cohort of 82 HCV-infected patients undergoing DAA treatment. Serum chemerin was positively associated with leukocyte count and negatively with markers of hepatic function and the model of end-stage liver disease (MELD) score. Low circulating chemerin levels significantly correlated with advanced liver fibrosis and cirrhosis as measured by the fibrosis-4 (FIB-4) score, the aminotransferase/platelet (AST/PLT) ratio index (APRI) score and the non-alcoholic fatty liver disease (NAFLD) score. Chemerin did not correlate with viral load or viral genotype. Treatment with DAAs did not improve MELD score and leukocyte count within the observation period, up to three months after the end of DAA treatment. Accordingly, chemerin levels remained unchanged during the treatment period. We conclude that low circulating chemerin is a noninvasive biomarker for hepatic dysfunction and advanced liver fibrosis and cirrhosis in HCV infection.